(untitled) (Mustansiria Dental Journal, 2018)
Viral hepatitis is a major public health problem, occurring endemically in all areas of the world. Unlike hepatitis A, hepatitis B does not generally spread through water & food. Instead, it is transmitted through body fluids; prevention is thus the avoidance of such transmission. This study included a total of 43patients who attended outpatient’s maxillofacial clinic, in Ramadi Teaching Hospital, Ramadi city. Results showed that out of the 43 patients 3 cases turned out to be Hbs Ag positive. Contact with blood and blood products, or contaminated saliva, surgeons and dentists are more at risk of this is a first investigation into the prevalence of acquiring HBV. All unvaccinated adults are at risk for HBV infection should be vaccinated. Hepatitis B vaccine is made from a part of the hepatitis B virus.